Identification of Phenylpyrazolone Dimers as a New Class of Anti‐Trypanosoma cruzi Agents. (23rd August 2019) - Sijm, Maarten; Siciliano de Araújo, Julianna; Ramos Llorca, Alba; Orrling, Kristina; Stiny, Lydia; Matheeussen, An; Maes, Louis; de Esch, Iwan J. P.; de Nazaré Correia Soeiro, Maria; Sterk, Geert Jan; Leurs, Rob
Abstract: Chagas disease is becoming a worldwide problem; it is currently estimated that over six million people are infected. The two drugs in current use, benznidazole and nifurtimox, require long treatment regimens, show limited efficacy in the chronic phase of infection, and are known to cause adverse effects. Phenotypic screening of an in‐house library led to the identification of 2, 2′‐methylenebis(5‐(4‐bromophenyl)‐4, 4‐dimethyl‐2, 4‐dihydro‐3 H ‐pyrazol‐3‐one), a phenyldihydropyrazolone dimer, which shows an in vitro pIC50 value of 5.4 against Trypanosoma cruzi . Initial optimization was done by varying substituents of the phenyl ring, after which attempts were made to replace the phenyl ring. Finally, the linker between the dimer units was varied, ultimately leading to 2, 2′‐methylenebis(5‐(3‐bromo‐4‐methoxyphenyl)‐4, 4‐dimethyl‐2, 4‐dihydro‐3 H ‐pyrazol‐3‐one (NPD‐0228) as the most potent analogue. NPD‐0228 has an in vitro pIC50 value of 6.4 against intracellular amastigotes of T. cruzi and no apparent toxicity against the human MRC‐5 cell line and murine cardiac cells. Abstract : Chagas disease is currently treated with only two drugs, benznidazole and nifurtimox, both of which show limited efficacy and certain adverse effects. In this study, phenotypic screening and subsequent optimization led to a bromophenyldihydropyrazole dimer (NPD‐0228), which is inactive against the bloodstream (trypomastigote) form of T. cruzi, but shows sub‐micromolar potency on the intracellular (amastigote) forms of the various parasite strains that are clinically relevant. As benznidazole is most active against the bloodstream form, NPD‐0228 might be well suited to combination treatments.